Member States’ Compliance with EU Law in 2018 in the Field of Internal Market (Journal of Legal Studies, 2018)
The present text is dedicated to analysing the situation of Member States‘ compliance with EU law in the field of Internal Market because it is one of the most important aspects of the process of European consolidation. In the introductory part we presented the central role of the European Commission because it is the institution that monitors the implementation of the EU law in the national legal order of each Member State. At the centre of our analysis is the 2017 Annual Report of the European Commission. Here we presented in a schematic manner the European norms that the Member States had to implement in their legal order in 2017. We concluded our research by presenting the evolution of this complex process with reference to the data furnished by the Single Market Scoreboard. The situation did not know a significant improvement in the process of Member States‘ compliance with EU law. We can see that things evolved but we consider that this evolution could have been better if Member States would have dedicated more attention to this process.